2012
DOI: 10.2478/v10290-012-0019-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Spirotetramat in the Control of Pear Psylla (Cacopsylla Pyri L.) on Pear Trees in Poland

Abstract: The effectiveness of spirotetramat in the control of pear psylla (Cacopsylla pyri) on pear trees was investigated in five field experiments, carried out in years 2009- 2011. One or two treatments were applied in June; the first treatment in the early stage of larvae hatching from eggs deposited by females from the summer generation, whilst the second application was carried out about two weeks later. In all the experiments, spirotetramat as Movento 100 SC applied at a dose of 2.25 l/ha effectively reduced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Given that in summer, the second‐ and third‐generation psylla population, and thereby honeydew amount, increase, and successful control will be harder. Erler and Cetin () reported that treatment of overwintered adults with insecticides is too effective to control C. pyri , but according to the present study, and similar reports about C. pyri (Bues et al ()) and C. pyricola (van de Baan et al (); van de Baan and Croft ()) have shown the best period for insecticide treatment for efficient control is treatment against the first generation, at the time when eggs are laid by females as well as during the egg hatching and the larvae appearance (Jaworska, Olszak, Łabanowska, & Korzeniowski, ). At this time of year, there is not much honeydew yet, and psylla are more susceptible, which would likely lead to better results and the reduction in damage during the next summer.…”
Section: Discussionsupporting
confidence: 69%
“…Given that in summer, the second‐ and third‐generation psylla population, and thereby honeydew amount, increase, and successful control will be harder. Erler and Cetin () reported that treatment of overwintered adults with insecticides is too effective to control C. pyri , but according to the present study, and similar reports about C. pyri (Bues et al ()) and C. pyricola (van de Baan et al (); van de Baan and Croft ()) have shown the best period for insecticide treatment for efficient control is treatment against the first generation, at the time when eggs are laid by females as well as during the egg hatching and the larvae appearance (Jaworska, Olszak, Łabanowska, & Korzeniowski, ). At this time of year, there is not much honeydew yet, and psylla are more susceptible, which would likely lead to better results and the reduction in damage during the next summer.…”
Section: Discussionsupporting
confidence: 69%
“…Reissig and Combs (2009) reported on high affectivity in the controlling of San Jose scale, green apple aphid and wooly apple aphid after treatment with Movento 240 SC. According to Jaworska et al (2012) Movento 100 SC also showed high efficacy in the control of pear psylla on pear trees. It is important for the integrated plant protection management that on plants treated with spirotetramat, some beneficial fauna such as Phytoseiidaelarvae and adults as well as eggs were noted.…”
Section: Resultsmentioning
confidence: 99%
“…Promising results in the control of aphids and other pests were obtained using the new product spirotetramat as Movento 100 SC, developed and introduced by Bayer CropScience (Cantoni et al 2008). Application of Movento 100 SC also reduced pear psylla population (Cacopsylla pyri L.) on pear trees (Jaworska et al 2012) and strawberry mite (Phytonemus pallidus Banks, syn. Tarsonemus fragariae Zimm.)…”
Section: Introductionmentioning
confidence: 95%
“…Seven psylla control treatments were performed during 2017, while there were six treatments (Tables 1, 2) during 2018, considering the possibility of weather conditions, as well as critical thresholds. In Croatia, a need for extra psylla control treatments is evident especially during the summer months, being in contrast to Poland, where only several treatments are usually carried out because of their possibility to control the first generation (Jaworska et al, 2012). In Turkey, usual practice against psylla is the appliance of six to eight insecticidal treatments per year (Erler et al, 2013), very similar to the Croatian practice.…”
Section: Resultsmentioning
confidence: 99%